How can businesses operating in the food system accelerate improvement in nutrition? - Haddad, Lawrence (International Food Policy Research Institute, 2019)
This chapter outlines some of the actions that businesses can take to improve nutrition outcomes and what governments and civil society can do to incentivize them to do so. The chapter argues that a failure to incentivize businesses to do more to improve nutrition results in missed opportunities to meet the UN Sustainable Development Goal target of ending malnutrition by 2030.